Peptides and Peptidomimetics as Tools to Probe Protein-Protein Interactions – Disruption of HIV-1 gp41 Fusion Core and Fusion Inhibitor Design - Cai, Lifeng; Shi, Weiguo; Liu, Keliang (IntechOpen, 2012)
None